Satisfaction of quantity surveying students towards online distance learning (ODL) during COVID-19 pandemic / Abdul ‘Izz Mohamad Kamil ... [et al.] - Mohamad Kamil, Abdul ‘Izz; Ismail, Noor Akmal Adillah; Hassan, Ahmad Arzlee; Raja Muhammad Rooshdi, Raja Rafidah; Marhani, Mohd Arif (Universiti Teknologi MARA, 2022)
When the Covid-19 pandemic started in 2019, it affected all industries and businesses around the globe including education institutions. All schools and universities required closures to avoid the widespread of the virus, therefore the mechanism to continue teaching and learning was transformed into online method, known as Online Distance Learning (ODL). However, many issues and challenges were recognized with regard to this transition of ODL conduct such as poor internet connection, lack of understanding via online teaching as compared to face-to-face method, insufficient online facilities, and many more. Hence, this paper aims to investigate university students’ satisfaction towards ODL during Covid-19 pandemic. A survey using questionnaire was conducted amongst Semester 1 to 6 Quantity Surveying students at Universiti Teknologi MARA, Shah Alam, Malaysia. The survey results were then analysed using SPSS tools. Findings from the survey found that most of the students satisfied with the ODL platform used for their online classes, however standardisation on the platform utilization amongst the courses are needed to stimulate better ODL experience. Although they also satisfied with the lecturers’ teaching and learning approaches during ODL, they expected that the university could assist them more on providing sufficient online facilities. This paper significantly contributes towards adding more literature to existing research regarding perspectives on ODL performance, concerning the factors influencing the students’ satisfaction mainly on the quality of ODL implementation approaches.